Integrated Circuit Test Engineering Modern Techniques - Grout, Ian A. (Springer London : Imprint: Springer, 2006)
Nearly sixty years ago, the first successful demonstration of the transistor proved to be the herald of a new era of microelectronics. The ever-increasing complexity and functional speed of microelectronic circuits now containing tens of millions of transistors demand appropriate and rigorous test engineering activities during development and production. Test engineering must also be more closely interwoven with microelectronic design. An understanding of circuit test engineering is vital to any student desiring a career involving any stage in the design or manufacture of integrated circuits. Taking a three-pronged approach - dealing with test engineering from traditional-test, design and manufacturing view-points - Integrated Circuit Test Engineering encapsulates the subject as it stands today. After an introduction covering background from basic testing rules to trends in technology, the reader learns about: • fabrication processes; • a diverse and complete range of detailed tests and procedures calculated to teach you all the tests you will require and how to choose which one(s) to use; • how to design for testability; • fault simulation; • automatic test equipment and • the economics of testing. From a practical perspective, the text includes: • A range of worked examples and exercises together with well-organized references and bibliography to aid further enquiry. • An introduction to various software such as MATLAB® and Spice explaining their use in testing together with that of IEEE-standard hardware-description languages Verilog®-HDL and VHDL. • A series of experiments based on material which can be freely downloaded from springeronline.com instructing you in the construction of a hardware test arrangement for MS Windows PCs (functionality, schematic and printed-circuit-board layout)with Visual Basic programs to drive the experiments. Integrated Circuit Test Engineering provides a thorough-going and illuminating introduction to test engineering in analogue, digital and mixed-signal integrated circuits. This text is a valuable practical learning tool for advanced undergraduate and graduate electronic engineering students, an excellent teaching resource for their tutors and a useful guide for the practising electronic engineer.